Auggie & me : three wonder stories - Palacio, R. J. (Alfred A. Knopf, 2015)
Three previously-published novellas that shed further light on the world of Auggie Pullman, an ordinary boy with an extraordinary face, set before he entered Beecher Prep and during his first year there and told from other characters' points of view. "The Julian Chapter" reveals why the bully dislikes Auggie so much. "Pluto" is about the lifelong friendship between Auggie and Christopher. And, finally, "Shingaling" offers a view of how the girls at Beecher Prep see Auggie when he first comes on the scene.